Analysis of physical load among professional soccer players during matches with respect to field position - Bujnovsky, D.; Maly, T.; Zahalka, F.; Mala, L. (Journal of Physical Education and Sport, 2015)
The aim of the study was to assess the level of internal physical load among professional soccer players during training matches and determine differences in size of physical load among field positions (fullbacks, central defenders, wide midfielders, central midfielders, attackers). The screened sample consisted of 13 players of the highest league (average age 23 ± 3.8 years, average body height: 183.1 ± 6.2 cm, average body weight: 74 ± 3.9 kg). Players` physical load was observed during three international training matches with respect to different field positions using Polar Team 2 heart rate monitor. The size of physical load was evaluated according to the level of heart rate and load duration in five zones that were set according to load intensity. These were classified as a zone under the aerobic threshold, zone of aerobic threshold (± 5 beats), zone between aerobic and anaerobic threshold, zone of anaerobic threshold (± 5 beats) and zone over anaerobic threshold. The results showed differences in players` load with regards to their field positions. The highest demands on physical load at high intensity (over anaerobic threshold) were found in central midfielders (21.8 ± 7.8 %) and attackers (17.8 ± 3.8 %). On the contrary, the greatest representation of central defenders was found below aerobic threshold (10.9 ± 3.8 %). Furthermore, results of the study showed that central midfielders spent 61.9 % of total time at, or over, the level of anaerobic threshold. Central defenders spent most time in lowest intensity (zone 1: 10.9 ± 3.8 %). Central midfielders and attackers achieved, in terms of effect size, a significant difference in time spent over the level of anaerobic threshold. The greatest differences between the first and second half-time were found in fullbacks, wide midfielders and central midfielders, while the lowest in central defenders and attackers players. Objectivized results of players` loading are the basis for designing team, group and individual training programmes reflecting the requirements of different field positions.